Magnetic Field of the Quasar 1604+159 from Parsec to Kiloparsec Scale - Xu-Zhi Hu; Xiaoyu Hong; Wei Zhao; Liang Chen; Wei-Yang Wang; Linhui Wu (The Astrophysical Journal, 2024)
We present a multifrequency polarimetric study for the quasar 1604+159. The source was observed at the L band with the American Very Long Baseline Array and the L , X , and U bands with the Very Large Array. These observations provide different resolutions from mas to arcsec, enabling us to probe the morphology and magnetic field from tens of parsec to hundreds of kiloparsec scale. We detect a symmetrical Fanaroff–Riley Class I–like structure. The source has several lobes and bulges, forming a cocoon shape. The polarization is normal to the edges of the structure with high fractional polarization up to ∼60%. Two hotspots are observed at the eastern and western sides of the source, located symmetrically relative to the core. The flux density ratio (>1.5) between the two hotspots suggests the Doppler beaming effect exists at a large scale. The polarized emission in the hotspots also shows a symmetrical structure with an oblique direction from the jet direction. In general, the jet propagates in a collimating structure with several bends. Polarization is also detected perpendicular to the local jet from ∼100 mas to ∼1″. The jet shows strong polarized intensity and high fractional polarization at the bending edges. We discuss the possible origins of the observed structure and magnetic field.